Effect of ginger oil on the sensory and chemical changes of fish finger (sarda sarda, heckel 1843) during refrigerated storage - Emir Çoban, O. (My University, 2013)
This study was examined the effect of ginger oil (0.5% and 1%) on chemical and sensorial quality and production of fingers from Sarda sarda. The amounts of moisture, crude ash, salt, pH, TVB-N and TBA in fillet were 77.16%,1.02% 0.59%, 6.43, 8 mg/100 g, 0.72 mgMDA/kg, respectively, while fish finger paste was found to be 56.6%, 2.97%, 2.95%, 6.10, 7.76 mg/100 g, 0.69 mgMDA/kg, respectively. There was no significant difference between groups in terms of moisture, crude ash, and salt amount (p > 0.05). However, significant differences were found between groups in terms of pH, TVB-N and TBA values (p < 0.05) during storage. It was observed that the addition of ginger oil at 1% to fish fingers increased the shelf life of the products while the addition of ginger oil made a positive effect on sensory quality. In conclusion, the addition of 1% ginger oil to fish fingers allowed for an acceptable shelf life for up to 17 days at 4°C. © All Rights Reserved.
Keywords: Chemical quality; Essential oils; Fish finger; Ginger oil; Sarda sarda